Thermodynamic stability of gilded copper and pigments at high relative humidity and at environmental conditions of Lima, Perú - Alviz-Meza, A. (2021)
Cultural heritage materials are affected by diverse environmental agents such as humidity, temperature, and pollution. This work focuses on studying the thermodynamic stability of Peruvian heritage materials such as gilded coppers and pigments within two scenarios: one under ambient conditions and the other under accelerated conditions established by the ASTM D 2247 standard. In both cases, the HSC Chemistry 6 software was implemented. The general results obtained for gilded coppers showed that by varying the relative humidity from 75% and 14 °C to 80% and 26 °C, the corrosion products move from CuO to Cu(OH) 2. In addition, to Cu2Cl(OH)3-Atacamite-in the presence of chlorin. On the other hand, for hematite (Fe 3O 2), vermilion (HgS), and Minium (Pb 3O 4) pigments, we found that at ambient conditions, with NO 2 and SO 2, they give rise to goethite (FeO(OH)), mercury sulfate (HgSO 4) and lead nitrate (Pb(NO) 3), respectively. These changes also modify the natural colour of pigments, where goethite gives rise to a brownish red, mercury sulfate is colorless and lead nitrate is white. This paper is a quick theoretical way to understand how cultural heritage materials can physically degrade. Future experiment trials will contribute to set strategies towards the correct management of these heritage collections. © Published under licence by IOP Publishing Ltd.